DMTs and Covid‐19 severity in MS: a pooled analysis from Italy and France. Issue 8 (7th July 2021) - Sormani, Maria Pia; Salvetti, Marco; Labauge, Pierre; Schiavetti, Irene; Zephir, Helene; Carmisciano, Luca; Bensa, Caroline; De Rossi, Nicola; Pelletier, Jean; Cordioli, Cinzia; Vukusic, Sandra; Moiola, Lucia; et al.
Abstract: We evaluated the effect of DMTs on Covid‐19 severity in patients with MS, with a pooled‐analysis of two large cohorts from Italy and France. The association of baseline characteristics and DMTs with Covid‐19 severity was assessed by multivariate ordinal‐logistic models and pooled by a fixed‐effect meta‐analysis. 1066 patients with MS from Italy and 721 from France were included. In the multivariate model, anti‐CD20 therapies were significantly associated (OR = 2.05, 95%CI = 1.39–3.02, p < 0.001) with Covid‐19 severity, whereas interferon indicated a decreased risk (OR = 0.42, 95%CI = 0.18–0.99, p = 0.047). This pooled‐analysis confirms an increased risk of severe Covid‐19 in patients on anti‐CD20 therapies and supports the protective role of interferon.